Stereotactic Ablative Body Radiotherapy for the Treatment of Spinal Oligometastases. Issue 7 (July 2017) - Chang, J.H.; Gandhidasan, S.; Finnigan, R.; Whalley, D.; Nair, R.; Herschtal, A.; Eade, T.; Kneebone, A.; Ruben, J.; Foote, M.; Siva, S.
Abstract: Aims: To report multicentre outcomes of patients with spinal oligometastases treated with stereotactic ablative body radiotherapy (SABR). The primary objective was to estimate the widespread failure-free survival (WFFS) at 2 years – defined as freedom from metastases not amenable to local salvage therapy and death. Materials and methods: Patients with one to three metastases treated with spinal SABR between January 2010 and July 2014 at four academic institutions were included in this retrospective review. The median dose/fractionation was 24 Gy (range 16–52.5 Gy) in two fractions (range one to three) and the median biologically effective dose (α/β = 10) was 52.5 Gy (range 40–144.4 Gy). The WFFS, overall survival, freedom from local progression and toxicity rates were described using Kaplan–Meier statistics. Results: In total, 60 patients with 72 spinal metastases were analysed. The median follow-up was 21 months. Patients had a median age of 66 years, Eastern Cooperative Oncology Group performance 0–1 in 97% and metachronous oligometastases in 85%. The 1 and 2 year WFFS rates were 67% (95% confidence interval 55–80) and 59% (95% confidence interval 47–75), respectively. The 1 and 2 year overall survival rates were 90% (95% confidence interval 83–98) and 76% (95% confidence interval 64–91), respectively. The 1 and 2 year freedom from local progression were 92% (95% confidence interval 85–99) and 86% (95% confidence interval 75–99), respectively. There were four cases (6.7%) of vertebral compression fracture and no cases of radiation myelopathy. Conclusion: Despite the use of relatively low biological doses respecting spinal cord constraints, SABR results in excellent 2 year local control rates with low morbidity. Through careful selection of patients with oligometastases, most patients are alive and free from widespread metastases at 2 years. This cohort warrants further investigation in clinical trials of SABR. Highlights: 60 patients with oligometastases were treated with spinal stereotactic radiotherapy. The 2 year overall survival and local control rates were 76% and 86%, respectively. The 2 year widespread failure-free survival rate was 59%. The vertebral compression fracture rate was 6.7%, with no cases of myelopathy.